Estrategias lúdicas para el fortalecimiento de la equidad de género en los estudiantes de tercer grado de la Escuela de Educación Básica ‘‘ Fe y Alegría”, del cantón Riobamba, provincia de Chimborazo, durante el año lectivo 2022-2023. - Ramos Montesdeoca, Adriana Elizabeth (2023)
This research work aimed to analyze playful strategies for the strengthening of gender equity in third-grade students of the "Fe y Alegría" School of Basic Education in the city of Riobamba, a guide to playful strategies was designed, which is essential to work equity in the classroom. It was considered necessary to start with a bibliographical review of the recreational process as a way to follow to achieve the strengthening of gender equity, regarding it as a mechanism for good coexistence. The population was considered non-probabilistic and intentional, comprised of 36 third-grade students of Basic General Education. The research methodology was governed by a qualitative approach, with a descriptive level, non-experimental and cross-sectional design. An observation sheet addressed to third-grade students was also used as a data collection instrument, with which the necessary data for this work was obtained. As one of the reflected results, the lack of equity among the students is determined, since at the moment of interacting and carrying out work in groups, discriminatory actions were evidenced, and it is there it is essential to have identified that there is an excellent variety of playful strategies that allow the strengthening of gender equality which can be used to work in the classroom and with This helps the integral learning of the students.